Steady state heat transfer analysis in a rectangular moving porous fin - Partner L. Ndlovu; Raseelo J. Moitsheki (Propulsion and Power Research, 2020)
In this article, the variation of temperature distribution and fin efficiency in a porous moving fin of rectangular profile is studied. This study is performed using Darcy's model to formulate the governing heat transfer differential equation. The approximate analytical solution is generated using the variational iteration method (VIM). The power series solution is validated by benchmarking it against the numerical solution obtained by applying the Runge-Kutta fourth order method. A good agreement between the analytical and numerical results is observed. The effects of porosity parameter, Peclet number and other thermo-physical parameters, such as the power index of heat transfer coefficient, convective-conductive parameter, radiative-conductive parameter, thermal conductivity gradient and non-dimensional ambient temperature on non-dimensional temperature are also studied and explained. The results indicate that the fin rapidly dissipates heat to the ambient temperature with an increase in the Peclet number, convection-radiation parameters and the porosity parameter.